Irreversible inhibition of BoNT/A protease: proximity-driven reactivity contingent upon a bifunctional approach. Issue 6 (19th May 2021) - Turner, Lewis D.; Nielsen, Alexander L.; Lin, Lucy; Pellett, Sabine; Sugane, Takashi; Olson, Margaret E.; Johnson, Eric A.; Janda, Kim D.
Abstract : A proximity-driven covalent bond with intrinsically less reactive warheads has been made possible by using a metal-chelating anchor for directed targeted covalent modification of Cys165 within the BoNT/A protease. Abstract : Botulinum neurotoxin A (BoNT/A) is categorized as a Tier 1 bioterrorism agent and persists within muscle neurons for months, causing paralysis. A readily available treatment that abrogates BoNT/A's toxicity and longevity is a necessity in the event of a widespread BoNT/A attack and for clinical treatment of botulism, yet remains an unmet need. Herein, we describe a comprehensive warhead screening campaign of bifunctional hydroxamate-based inhibitors for the irreversible inhibition of the BoNT/A light chain (LC). Using the 2, 4-dichlorocinnamic hydroxamic acid (DCHA) metal-binding pharmacophore modified with a pendent warhead, a total of 37 compounds, possessing 13 distinct warhead types, were synthesized and evaluated for time-dependent inhibition against the BoNT/A LC. Iodoacetamides, maleimides, and an epoxide were found to exhibit time-dependent inhibition and their k GSH measured as a description of reactivity. The epoxide exhibited superior time-dependent inhibition over the iodoacetamides, despite reacting with glutathione (GSH) 51-fold slower. The proximity-driven covalent bond achieved with the epoxide inhibitor was contingent upon the vital hydroxamate–Zn 2+ anchor in placing the warhead in an optimal position for reaction with Cys165. Monofunctional control compounds exemplified the necessity of the bifunctional approach, and Cys165 modification was confirmed through high-resolution mass spectrometry (HRMS) and ablation of time-dependent inhibitory activity against a C165A variant. Compounds were also evaluated against BoNT/A-intoxicated motor neuron cells, and their cell toxicity, serum stability, and selectivity against matrix metalloproteinases (MMPs) were characterized. The bifunctional approach allows the use of less intrinsically reactive electrophiles to intercept Cys165, thus expanding the toolbox of potential warheads for selective irreversible BoNT/A LC inhibition. We envision that this dual-targeted strategy is amenable to other metalloproteases that also possess non-catalytic cysteines proximal to the active-site metal center.